2006
DOI: 10.1249/01.mss.0000183196.63081.6a
|View full text |Cite
|
Sign up to set email alerts
|

Power Output during Stage Racing in Professional Road Cycling

Abstract: Most of the competition time during the mass start stages was spent at intensities near the LT. Compared with power output, heart rate measurement underestimated the time spent at intensity zones 1 and 3, and overestimated the time spent in zone 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
99
2
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(110 citation statements)
references
References 27 publications
8
99
2
1
Order By: Relevance
“…zone 2), 22% (zone 3), 13% (zone 4) and 13% (zone 5) of 3-h hilly world cup cycling races into the intensity zones assessed previously during laboratory testing. Similarly, the present data are comparable with a study of Vogt et al (2006) concerning a 6-stage race of 215-min mean time performed by male professional cyclists. The distribution of time in the different intensities was 58% for zone 1, 14% for zone 2 and 28% at intensities higher than an increase in 1 mM above the lactate threshold (zone 3).…”
Section: Similarities Between Elite Female and Male Triathletessupporting
confidence: 89%
“…zone 2), 22% (zone 3), 13% (zone 4) and 13% (zone 5) of 3-h hilly world cup cycling races into the intensity zones assessed previously during laboratory testing. Similarly, the present data are comparable with a study of Vogt et al (2006) concerning a 6-stage race of 215-min mean time performed by male professional cyclists. The distribution of time in the different intensities was 58% for zone 1, 14% for zone 2 and 28% at intensities higher than an increase in 1 mM above the lactate threshold (zone 3).…”
Section: Similarities Between Elite Female and Male Triathletessupporting
confidence: 89%
“…Most of the studies on road cycling have examined the exercise intensity of long stage races (Giro d'Italia, Tour de France, Vuelta a Espana). Only two studies have described the exercise intensity of short stage races in professional (Vogt et al 2006) and amateur cyclists (Palmer et al 1994). Vogt et al (2006) showed a mean HR during four stages ranging from 140 to 144 bpm (the HR during the uphill time trial was 169 bpm).…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have described the exercise intensity of short stage races in professional (Vogt et al 2006) and amateur cyclists (Palmer et al 1994). Vogt et al (2006) showed a mean HR during four stages ranging from 140 to 144 bpm (the HR during the uphill time trial was 169 bpm). Unfortunately, they did not report the HR MAX making the comparison with the present study not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Power has been used to describe performance in cycling [23,24], rowing [25] and kayakers [26]. Power in swimming has been difficult to measure and to define also.…”
Section: Discussionmentioning
confidence: 99%